Membangun Keberlanjutan Usaha UMKM Makanan dan Minuman Berbasis Manajemen Keuangan di Kabupaten Pemalang - Nurchayati; Bambang Riyadi; Suparmi; Siti Aminah; Asta Nugraha (Fakultas Ekonomi, Universitas PGRI Adi Buana Surabaya, 2023)
This community service aims to help improve the sustainability of food and beverage Micro, Small, and Medium Enterprises (UMKM) in Pemalang Regency through the effective application of financial management. Pemalang Regency, like many regions in Indonesia, has a thriving UMKM sector in the food and beverage industry. However, many of them face various issues, including a lack of understanding of good financial management. This community service includes training and mentoring for UMKM owners in the effective implementation of financial management. Business owners are provided with an understanding of the importance of proper financial record-keeping, budget planning, cash management, and wise investment. They are also given access to simple accounting software to assist them in recording financial transactions. The impact of this community service is highly positive. Owners of food and beverage UMKM in Pemalang Regency can optimize the use of their financial resources, improve operational efficiency, and generate higher profits. They are also better equipped to handle financial risks and have improved access to sources of financing. Furthermore, this activity contributes to increased employment opportunities in the region, supports the local economy, and enhances the quality of life for the surrounding community. More competitive UMKM also enhances the competitiveness of Pemalang Regency in the regional market. In conclusion, this community service has successfully enhanced the sustainability of food and beverage UMKM in Pemalang Regency through the effective implementation of financial management. With improved understanding and skills in financial management, UMKM can better address financial challenges and contribute to local economic growth.